2021
DOI: 10.3390/antibiotics10010053
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Use of Tedizolid in Osteoarticular Infections: Benefits among Oxazolidinone Drugs

Abstract: Background: To evaluate the efficacy and safety of long-term use of tedizolid in osteoarticular infections. Methods: Multicentric retrospective study (January 2017–March 2019) of osteoarticular infection cases treated with tedizolid. Failure: clinical worsening despite antibiotic treatment or the need of suppressive treatment. Results: Cases (n = 51; 59% women, mean age of 65 years) included osteoarthritis (n = 27, 53%), prosthetic joint infection (n = 17, 33.3%), and diabetic foot infections (n = 9, 18%); whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…It has been shown that tedizolid has lower steady-state tissue/plasma ratios in rat bone and brain in comparison to linezolid, which may be a mechanistic explanation of the observed low incidence of hematological adverse effects and central nervous system interactions [ 3 ]. With a median duration of 188 (IQR, 62–493) days, the tedizolid duration in this report far surpasses both the time period when adverse effects associated with linezolid would be expected to be observed as well as other published reports on long-term tedizolid use [ 6 , 10 , 11 , 13 ]. Two recent studies that evaluated the safety profile of tedizolid exhibited similar rates of adverse effects (11.1% and 5.9%, overall; 8.6% and 0%, hematologic-related); however, the durations of tedizolid exposure in these investigations were shorter compared with those described in this report (median of 28 [IQR, 14–59] and 29 [IQR, 15–44] days) [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 66%
“…It has been shown that tedizolid has lower steady-state tissue/plasma ratios in rat bone and brain in comparison to linezolid, which may be a mechanistic explanation of the observed low incidence of hematological adverse effects and central nervous system interactions [ 3 ]. With a median duration of 188 (IQR, 62–493) days, the tedizolid duration in this report far surpasses both the time period when adverse effects associated with linezolid would be expected to be observed as well as other published reports on long-term tedizolid use [ 6 , 10 , 11 , 13 ]. Two recent studies that evaluated the safety profile of tedizolid exhibited similar rates of adverse effects (11.1% and 5.9%, overall; 8.6% and 0%, hematologic-related); however, the durations of tedizolid exposure in these investigations were shorter compared with those described in this report (median of 28 [IQR, 14–59] and 29 [IQR, 15–44] days) [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 66%
“…However, because of the small sample size ( n = 40) of the study, the long-term safety of TDZ necessitates further investigations. Studies with slightly longer durations (mean of 27–29 days) support these findings [ 102 – 104 ]. In ESTABLISH 1 and 2 trials, neurological (~ 9%) and dermatological (~6%) toxicities were almost equally often reported for both TDZ and LNZ, which were well supported in other studies [ 14 , 90 , 91 , 105 ].…”
Section: Pharmacodynamicsmentioning
confidence: 75%
“…Tedizolid has been used off-label with a varying degree of success in the treatment of prosthetic joint infections, osteomyelitis, central nervous system infections, mycobacterial infections, and pneumonia. 32,124,125 Unlike linezolid, which is administered twice daily, tedizolid is given once daily. 32,123 Another advantage is that tedizolid appears to cause fewer hematological adverse effects and fewer interactions with serotonergic agents than linezolid; however, long-term safety data are not yet available.…”
Section: Antibiotics and Related Biologics Approved By The Fda From J...mentioning
confidence: 99%
“…32,123 Another advantage is that tedizolid appears to cause fewer hematological adverse effects and fewer interactions with serotonergic agents than linezolid; however, long-term safety data are not yet available. 123 -125 Oral tedizolid inhibits the breast cancer resistance protein (BCRP) in the intestine, and caution is required when coadministering oral BCRP substrates. 32…”
Section: Antibiotics and Related Biologics Approved By The Fda From J...mentioning
confidence: 99%